Sobre el desarrollo de la lógica borrosa - Portela, Oscar (ENDOXA, 2006)
Over the last decades, a new branch has been added to the corpus of formal theories of reasoning: fuzzy logic. Showing an impressive potencial, its development has quickly evolved from the theoretical playground to the practical applications, with a vast number of actual researchers joining their efforts to yield further advancements. However, tracing a faithful history on this development is, as happens every time such attempt is pretended, somehow difficult because of a number of factors associated with the task. One of the consequences is that, being usually based on a personal, subjective point of view, the results given are bound to the chronicler opinions, as well as their relative valué. Aiming to offer an alternative to this approach, some steps are here presented by means of severa! indicators derívate from the study of a comprehensive set of literature on the subject. A perspective established over such elements will, hopefiílly, enable a view on the history of fuzzy logic oriented to a clearer scope.